Sosialisasi Peluang dan Tantangan Era Teknologi 4.0 Bagi Siswa SMK Panca Bakti Rakit - Retno Waluyo; Ito Setiawan; Zulfa Chafidz Nur; Armeyta Putri Tanzilla (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
Currently, students cannot be separated from social media, social media is used to interact and communicate with people they know or do not know through online. Students today tend to be fanatical so that their lives are greatly influenced by technological developments. This also happened to students at Panca Bhakti Rakit Vocational School. Problems that occur in students such as lack of understanding about the use of social media, the benefits of social media, the wrong use of the internet for example to open prohibited sites, the number of frauds, lack of knowledge about industri 4.0, it is necessary to socialize to prepare for the industrial revolution 4.0 in order to have a positive impact from the industrial revolution 4.0, and not fall into its negative impact. The purpose of the training is to introduce the industrial revolution 4.0 to students to improve knowledge, skills and expertise in the field of technology. There are 3 stages of training starting from preparation, implementation and evaluation. The result of the training is to increase students' knowledge of the development of industri 4.0, especially about technological developments.